Chronic degenerative diseases in elderly: physiotherapeutic data - doi:10.5020/18061230.2011.p221 - Lais Keylla Felipe; Anita Zimmermann (Universidade de Fortaleza, 2012)
Objective: To assess the most frequent chronic diseases in the elderly population of a private clinic of Physiotherapy. Methods: We assessed medical records of clients who received treatment at a Physiotherapy clinic in the period 2005 to 2008, looking for chronic diseases as diagnosis and/or related to them. Of these, we selected those which contained birth date and/or aged sixty-five years or above. An instrument like a check list, developed by the researchers, identified: quantity, gender, medical diagnosis and comorbidities. For quantification of variables we applied simple percentage calculation. Results: In the study period, there were four hundred fifty-eight records, of which forty-nine corresponded to the survey's inclusion criteria. The majority 59.2% (n=29) referred to the year 2008; 26.6% (n=13) being males and 73.4% (n=36) females. The most commonly found diagnosis comprised osteoarthritis 57.1% (n=28), fracture and/or history of fractures 24.4% (n=12) and other diagnosis 48.9% (n=24). Associated chronic diseases included diabetes mellitus 18.3% (n=9) and systemic hypertension 57.1% (n=23). Conclusion: Chronic degenerative diseases in elderly have received increasing attention from health professionals; osteoarthritis being the most common diagnosis in this study, followed by fracture and/or history of fractures. The comorbidities represented a greater negative impact in the quality of life of elderly.